Supramolecular Inhibition of Amyloid Fibrillation by Cucurbit[7]uril1. Issue 29 (19th May 2014) - Lee, Hong Hee; Choi, Tae Su; Lee, Shin Jung C.; Lee, Jong Wha; Park, Junghong; Ko, Young Ho; Kim, Won Jong; Kim, Kimoon; Kim, Hugh I.
Abstract Amyloid fibrils are insoluble protein aggregates comprised of highly ordered β‐sheet structures and they are involved in the pathology of amyloidoses, such as Alzheimer's disease. A supramolecular strategy is presented for inhibiting amyloid fibrillation by using cucurbit[7]uril (CB[7]). CB[7] prevents the fibrillation of insulin and β‐amyloid by capturing phenylalanine (Phe) residues, which are crucial to the hydrophobic interactions formed during amyloid fibrillation. These results suggest that the Phe‐specific binding of CB[7] can modulate the intermolecular interaction of amyloid proteins and prevent the transition from monomeric to multimeric states. CB[7] thus has potential for the development of a therapeutic strategy for amyloidosis.